2018
DOI: 10.1002/tea.21517
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the science achievement models for low and high achieving schools and gender differences in Turkey

Abstract: A science achievement model was separately investigated for students in low and high achieving schools (LAS and HAS) in Turkey. Then, gender differences based on variables that significantly contributed to each achievement model were investigated. The student‐level variables that were under investigation for multiple regression analyses include attitudes toward science, epistemological beliefs, metacognition, views on science teaching, and socioeconomic status (SES). The science achievement scores of students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 65 publications
(153 reference statements)
0
15
0
4
Order By: Relevance
“…Previous studies had indicated the association between academic achievement with self-efficacy and SC. [ 16 17 28 ] It is emphasis high level of self-efficacy can decrease the educational burnout and cause ability in the adolescents’ education. [ 29 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had indicated the association between academic achievement with self-efficacy and SC. [ 16 17 28 ] It is emphasis high level of self-efficacy can decrease the educational burnout and cause ability in the adolescents’ education. [ 29 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…There has been broad agreement on what comprises core components of metacognition including across school and university study (Lai, 2011). In general terms, metacognition is the form of cognition whose subject is cognition (Acar, 2019). Ongoing agreement concurs with Flavell's (1976) early characterization that metacognition consists of metacognitive knowledge and metacognitive experiences and that metacognition 'regulates any aspect of any cognitive endeavor' (p. 906).…”
Section: De Nition Of Metacognitionmentioning
confidence: 91%
“…Gender differences in students' attitudes toward science have been observed in various continents, including Africa by Reddy (2017), America by Pahlke et al (2014), Europe by Tytler and Osborne (2012), Asia by Fulmer et al (2019), and Australia and other parts of the world by UNICEF (2020), with some studies attempting to establish the differences with respect to school type (Acar, 2017). According to research evidence reported by the Programme for International Student Assessment (PISA, 2015), not only are fewer girls than boys performing at or above Level 5 in science in countries such as Australia, Canada, Germany, Hungary, Singapore, Spain, and Sweden, but girls are also less likely than boys to expect to advance their career in a STEM field (UNESCO, 2020).…”
Section: Review Of Literaturementioning
confidence: 99%